Respuesta :
A(7, 3) is translated to A'(16,-9)
7 + 9 = 16
3 - 12 = -9
Rule:
(x,y) --->(x +9 , y - 12)
Hope it helps
Answer:
[tex]\boxed{A(x,y)\rightarrow A'(x+9,y-12)}[/tex]
Step-by-step explanation:
We want to find the rule that translated the point A(7,3) to A'(16,-9).
Let the translation vector be [tex]\binom{a}{b}[/tex]
Then,
[tex]\binom{7}{3}+\binom{a}{b}=\binom{16}{-9}[/tex]
This implies that;
[tex]\binom{a}{b}=\binom{16}{-9}-\binom{7}{3}[/tex]
[tex]\Rightarrow \binom{a}{b}=\binom{16-7}{-9-3}[/tex]
[tex]\Rightarrow \binom{a}{b}=\binom{9}{-12}[/tex]
The translation rule is
[tex]A(x,y)\rightarrow A'(x+9,y-12)[/tex]